1992
DOI: 10.1093/oxfordjournals.humrep.a137595
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of androgen receptor in the human endometrium, decidua, placenta and pathological conditions of the endometrium

Abstract: The immunohistochemical localization of the androgen receptor in the human endometrium at various stages of the menstrual cycle and post-menopausal period, in decidua and placenta of early pregnancy, and in several pathological conditions of the endometrium has been investigated. At any phase of the menstrual cycle, both endometrial glandular cells and endometrial stromal cells showed positive nuclear staining. Endometrial stromal cells of the functional layer showed stronger staining than those of the basal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 0 publications
8
70
0
2
Order By: Relevance
“…Studies across species reported that ARs are expressed in theca cells, granulosa cells (GCs), and the oocyte of the follicle and throughout most stages of follicular development (Horie et al 1992, Chadha et al 1994, Hirai et al 1994, Suzuki et al 1994, Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000, Slomczynska & Tabarowski 2001, Gill et al 2004, Hampton et al 2004, Juengel et al 2006. However, their expression patterns may differ between ovarian cell types (Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000 and in most species, AR is abundant in the preantral/antral stages of follicular development but declines as follicles mature to the preovulatory stage (Horie et al 1992, Chadha et al 1994, Suzuki et al 1994, Duffy et al 1999, Hampton et al 2004, Juengel et al 2006. In fact, AR is expressed in cell-specific regions of human ovarian follicles at all stages of follicular development beyond the primordial phase (Rice et al 2007).…”
Section: Ar Expression and Regulationmentioning
confidence: 99%
“…Studies across species reported that ARs are expressed in theca cells, granulosa cells (GCs), and the oocyte of the follicle and throughout most stages of follicular development (Horie et al 1992, Chadha et al 1994, Hirai et al 1994, Suzuki et al 1994, Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000, Slomczynska & Tabarowski 2001, Gill et al 2004, Hampton et al 2004, Juengel et al 2006. However, their expression patterns may differ between ovarian cell types (Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000 and in most species, AR is abundant in the preantral/antral stages of follicular development but declines as follicles mature to the preovulatory stage (Horie et al 1992, Chadha et al 1994, Suzuki et al 1994, Duffy et al 1999, Hampton et al 2004, Juengel et al 2006. In fact, AR is expressed in cell-specific regions of human ovarian follicles at all stages of follicular development beyond the primordial phase (Rice et al 2007).…”
Section: Ar Expression and Regulationmentioning
confidence: 99%
“…The endometrium expresses testosterone receptors during the entire menstrual cycle, primarily in the endometrial functional layer [35]. Patients with hyperandrogenism secondary to polycystic ovary syndrome demonstrate lower levels of HOXA10 mRNA in the secretory phase, which might influence fertility in this group of patients [36].…”
Section: Hoxa-10/hoxa-10 Is Involved In the Organogenesis Of The Müllmentioning
confidence: 99%
“…The AR is expressed in primates (including humans) throughout the reproductive cycle, where it modulates follicular growth and maturation and other reproductive processes [39]. AR expression is also found in a very high proportion (up to 95%) of tumor tissue samples from ovarian cancers, and frequency of expression positively correlates with malignancy [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such conflict likely represents only one of many manifestations of sexual conflict over the regulation of hormonal systems, given the myriad pleiotropic effects of testosterone, estrogen and other hormones on physiological systems. While it might appear that females could evolve to optimize their sex-specific expression of the AR in the context of cancer risk, such changes may interfere with important aspects of female physiology [39], and recent evidence also suggests that repression of sexually antagonistic genes is often incomplete or unsuccessful. Indeed, research on Drosophila and other species indicates that the expression of sexually antagonistic genes in the ''wrong'' sex is pervasive and imposes a significant cost on adults [5,60].…”
Section: Introductionmentioning
confidence: 99%